A Fast and Easy ATP-Based Approach Enables MIC Testing for Non-resuscitating VBNC Pathogens - Robben, Christian; Witte, Anna Kristina; Schoder, Dagmar; Stessl, Beatrix; Rossmanith, Peter; Mester, Patrick (Frontiers in Microbiology, 2019)
Many bacteria enter the viable but non-culturable (VBNC) state to maximize resources and increase their tolerance to harmful conditions to cope with environmental stress, which has been described for a plethora of important human and foodborne pathogens. VBNC pathogens can potentially present a serious risk to human health as they are invisible to routine microbiological culture-based methods. Of high importance is the increased tolerance to antibiotics or disinfectant measures while in the VBNC state. The greatest remaining challenge for such investigations is the lack of an appropriate, cost-effective multi-species screening method due to experimental constraints. In this study, we investigated if de novo ATP production of cells in the VBNC state is a suitable indicator for overall cell viability that can be utilized to determine the minimum ATP inhibitory concentration (MAIC) of antibiotics and other antimicrobials. To validate this approach, heat-stress time-kill experiments were performed with both culturable and VBNC cells. We developed a comprehensive experimental setup and demonstrated the applicability of this VBNC-MIC assay for testing the tolerance of twelve strains of four important bacterial species (Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa and Listeria monocytogenes) in the VBNC state to eight important antimicrobials including four different antibiotics. We confirmed that bacteria in the VBNC state were resistant to all tested antibiotics (ampicillin, imipenem, ciprofloxacin and gentamycin) and additionally insensitive to disinfectants (benzalkonium chloride and trioctylmethalammonium chloride) and preservatives (bronopol and sodium azide). These data emphasize the need for further research regarding the characteristics of bacterial pathogens in the VBNC state and present the advantages and high-throughput capabilities of ATP determinations to investigate tolerance of VBNC pathogens to antimicrobials. The presented method should be helpful in order to identify appropriate countermeasures, treatments or disinfectants when confronted with bacterial pathogens in the VBNC state.